Specular gloss - Silvennoinen, Raimo; Peiponen, K. -E. (Kai-Erik), 1954-; Myller, Kari.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2008)
The aesthetic appearance of various objects is important to human beings. One measure of the quality of an object is its surface quality, which can be characterized with the concept of gloss. Nowadays measurement of the gloss is a routine off-line method in assessment of quality of product at various sectors of industry. The book gives a fresh treatment on the concept of gloss. Theoretical description will be on more general basis of optical physics than in other sources. The text will give a modern treatise of machine vision based glossmeters and furnish the ideas how to measure and analyse gloss from complex-structured objects. Innovations of machine vision and gloss data analysis by embedded micro-controllers and microprocessors are trademarks that fill the gaps of older textbooks. Key Features: - modern treatment of gloss - presents novel glossmeter based high technology - completes principle of machine vision - application in industrial environment - emphasis on pedagogical presentation - modern treatment of gloss - describes novel glossmeter-based high technology - presents principles of machine vision - gives applications in industrial environment - emphasis on pedagogical presentation.
Introduction -- Light reflection from ideal surface -- Light reflection from a rough surface -- Specular gloss -- Light sources for gloss measurement -- Detectors for gloss measurement -- Traditional glossmeters -- Modern glossmeters.
Includes bibliographical references (pages 413-479) and index.
Print version record.
Elsevier
Keywords: Specular reflectance; Specular reflectance -- Measurement; Optical measurements; SCIENCE -- Physics -- Optics & Light; Optical measurements; Specular reflectance; Specular reflectance -- Measurement; Electronic books